2009
DOI: 10.1111/j.1469-8749.2008.03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cerebral visual impairment with the L94 visual perceptual battery: clinical value and correlation with MRI findings

Abstract: In this article we describe visual perceptual abilities of a clinical population, referred for visual problems to our multidisciplinary team and assessed with the five computer tasks from the L94 visual perceptual battery. Clinical and neuroimaging findings were correlated with the findings on this task battery. Seventy children (35 males, 35 females) constituted our cohort. Age ranged from 4 to 20 years (mean 7y [SD 3y]). Forty children were born before 37 weeks gestational age. Thirty-six children had cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 25 publications
3
84
0
2
Order By: Relevance
“…In addition, a series of recent studies reported abnormal sensitivity to point-light biological motion, a stimulus containing form information [11], in preterm participants with periventricular brain injury (PVL), but not in agematched low-risk preterms [5][6][7]. Consistent with our results, significant disorders of form recognition have been reported in preterm children with PVL [12][13][14][15], but not in those without brain damage [16].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, a series of recent studies reported abnormal sensitivity to point-light biological motion, a stimulus containing form information [11], in preterm participants with periventricular brain injury (PVL), but not in agematched low-risk preterms [5][6][7]. Consistent with our results, significant disorders of form recognition have been reported in preterm children with PVL [12][13][14][15], but not in those without brain damage [16].…”
Section: Discussionsupporting
confidence: 91%
“…This raises the question of how brain damage is clinically defined. For example, children born preterm may have elevated levels of visual perceptual difficulties even with MRI scans reported as normal27; is a known risk factor sufficient? Currently, the component of Brain Integrity is only inferential and assumes that clinical visual symptoms originate at brain level.…”
Section: Discussionmentioning
confidence: 99%
“…Many children with CP have visual-spatial perceptual impairments despite typical or near-typical visual acuity (Akhutina, Foreman, Krichevets, & Vahakuopus, 2003;Ego et al, 2015;Menken, Cermak, & Fisher, 1987;Reed & Drake, 1990;Ortibus, Lagae, Casteels, Demaerel, & Stiers, 2009;Stadskleiv, Jahnsen, Andersen, & von Tetzchner, 2017). Ego et al (2015), in a systematic review of visual-perceptual impairments in children with CP, identified 15 studies which included one of five standardised tests that assessed visual perception.…”
Section: Mathematical Abilities Visual-spatial Abilities and Cerebrmentioning
confidence: 99%